Resilience: why should we think with care? - Catia Gregoratti; Mikael Linnell; Martina Angela Caretta (Global Social Challenges Journal)
Resilience has become a ubiquitous term. Individuals, communities and societies are increasingly called upon to be resilient and build resilience as a way to withstand and bounce back from compound climate-induced shocks, conflicts, health and economic crises. In this provocation we critically interrogate the potential that resilience holds for moving beyond a world marked by crises and widening inequalities. A multidisciplinary corpus of feminist scholarship conceives of resilience as a conservative and deeply exclusionary biopolitical device. Against this background, we argue that expressions of resilience from above and below firmly guided by principles of care can be seen as serving socially and environmentally just ends. We thus encourage scholars, particularly feminist scholars, to continue engaging and engaging more courageously with these two concepts in a collective effort to reclaim resilience as a transformatory device.